Measurement of carotid plaque burden: A tool for predicting and preventing dementia? - John J. Shin; Vladimir Hachinski; M. Reza Azarpazhooh; Aidin Shariatzadeh; J. David Spence (Cerebral Circulation - Cognition and Behavior, 2021)
Introduction: Carotid plaque burden is a strong predictor of stroke risk, and preventing stroke reduces the risk of dementia. Treating carotid plaque burden markedly reduces the risk of stroke. Methods: Among patients age 65–80 years attending a stroke prevention clinic, we identified those with a carotid plaque burden in the top 20% of Total Plaque Area (High TPA) and the bottom 20% (Low TPA) and performed cognitive tests: The Montreal Cognitive Assessment test (MoCA), the WAIS-III Digit Symbol-Coding Test (DSST) and Trail-Making Test (TMT) part A and B. Results: There were 31 patients recruited; 11 Low TPA (5 men) and 20 High TPA (17 men), p = 0.04. TPA was 35 ± 25 mm2 in the Low TPA vs.392 ± 169 mm2 in the High TPA group (0.0001). Patients with a high plaque burden had significantly worse performance on all the cognitive tests, all p< 0.05 Discussion: A high carotid plaque burden identifies patients at risk of cognitive impairment. Because carotid plaque burden is treatable, and treating it markedly reduces the risk of stroke, we suggest that measurement of plaque burden is a useful tool for both prediction of cognitive impairment, and prevention of dementia.